An analysis of the short story Copacabana Hong Kong, by Fausto Fawcett. (INSÓLITA - Revista Brasileira de Estudos Interdisciplinares do Insólito, da Fantasia e do Imaginário, 2026)
Creating dystopian narratives is a recurrent aspect in Fausto Fawcett’s works. As an example, the short story Copacabana Hong Kong describes Derek, an American scientist, as he makes his way towards the underwear cannon in order to shoot lingeries into the sky to try and control the atmospheric pollution. In this essay, we discuss the grotesque realism according to Bakhtin (1996) and the post-modernism according to Hutcheon (1991) to explore how Fawcett uses grotesque images of the body as well as interdiscursive references to build his dystopian scenario. We also consider the work of Ginway (2005) about Brazilian cyberpunk novels and their references to sexuality and Brazilian and Afro-Brazilian cultures.Keywords: Literature; Grotesque realism; Post-modern; Fausto Fawcett.